Inactivation of Dihydrostreptomycin and Spectinomycin by Staphylococcus aureus - Kawabe, Haruhide (1974)
Three types of Staphylococcus aureus strains were isolated with respect to streptomycin (SM) and spectinomycin (SPC) resistance, namely, SM(r)SPC(r), SM(r)SPC(s), and SM(s)SPC(r) (r, resistant; s, sensitive). Curing experiments and transduction analysis of strain MS7990 (SM(r).SPC(r).EM(r)) (EM, erythromycin) disclosed that the loci governing SM and SPC resistance are different and exist on different nontransferable plasmids (r factor), one plasmid carrying the genes governing SM resistance and another possessing the genes governing resistance to both SPC and EM. Strain MS7990 (SM(r).SPC(r)) inactivated both drugs by adenylylation. Similarly, the SM(r)SPC(s) and SM(s)SPC(r) strains inactivated SM and SPC, respectively, by adenylylation, although the adenylylated positions of both drugs have not been established as yet. The adenylylated SM in staphylococci was shown to be different from 3″-adenylyl-SM, indicating the possibility of the existence of a different enzyme from SM3″-adenylyl transferase demonstrated in Escherichia coli strains.